HUBUNGAN MENGKONSUMSI MINUMAN KERAS (ALKOHOL) TERHADAP RESIKO NYERI ULU HATI (GERD) PADA PEMUDA (USIA 19-25 TAHUN) DI KELURAHAN MAESA UNIMA KECAMATAN TONDANO SELATAN - Montovani, Glen K. R.; Bawiling, Nancy S.; Salam, Ilham (Yayasan Syalom Cipta Sumikolah, 2024)
Heartburn is a non-communicable disease that is still a global health problem. In general, heartburn usually begins with an irregular eating pattern so that the stomach becomes sensitive when stomach acid increases. Consuming alcoholic drinks is very dangerous for the body, because it contains ethanol as a psychoactive ingredient which can cause decreased consciousness. The impact of consuming alcohol can eliminate your sense of self-control, causing various diseases, one of which is heartburn. The aim of this research is to analyze the relationship between alcohol consumption and the risk of heartburn in young people (aged 19-25) in Maesa Unima Village, South Tondano District. This research is an analytical description research with a Cross Sectional Study approach which was conducted in Maesa Unima Village from October to November 2023 with a sample size of 35. This research was analyzed using univariate analysis which produces a frequency distribution for each variable and bivariate analysis to determine The impact of alcohol consumption on the risk of heartburn using the Chi Square test which is supported by the SPSS program. Based on the research results, a significant value of p=0.009 (<0.05) was obtained. From these results, it can be concluded that consumption of alcoholic beverages (alcohol) is related to the risk of heartburn in young people (aged 19-25 years) in Maesa Unima Village, South Tondano District.